2021
DOI: 10.1186/s12872-021-01851-8
|View full text |Cite
|
Sign up to set email alerts
|

The association between T wave inversion in leads with ST-elevation and patency of the infarct-related artery

Abstract: Background Up to over half of the patients with ST-segment elevation myocardial infarction (STEMI) are reported to undergo spontaneous reperfusion without therapeutic interventions. Our objective was to evaluate the applicability of T wave inversion in electrocardiography (ECG) of patients with STEMI as an indicator of early spontaneous reperfusion. Methods In this prospective study, patients with STEMI admitted to a tertiary referral hospital were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…6,7 In patients who have not received reperfusion therapies, early inverted T waves were shown to be a marker of spontaneous recanalization of the culprit artery. 8 Therefore, in this case, the patient experienced the acute, typical chest pain of AMI, but it resolved spontaneously. It is possible that the transition from the de Winter to Wellens pattern was associated with spontaneous recanalization (activation of fibrinolytic system or antithrombotic therapy) after acute total occlusion of the LAD, which was followed by partial reperfusion of the myocardium, because the coronary angiography results showed 95% stenosis but not total occlusion of the LAD.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…6,7 In patients who have not received reperfusion therapies, early inverted T waves were shown to be a marker of spontaneous recanalization of the culprit artery. 8 Therefore, in this case, the patient experienced the acute, typical chest pain of AMI, but it resolved spontaneously. It is possible that the transition from the de Winter to Wellens pattern was associated with spontaneous recanalization (activation of fibrinolytic system or antithrombotic therapy) after acute total occlusion of the LAD, which was followed by partial reperfusion of the myocardium, because the coronary angiography results showed 95% stenosis but not total occlusion of the LAD.…”
Section: Discussionmentioning
confidence: 78%
“…In patients with AMI who are undergoing thrombolytic therapy, studies have shown that early T wave inversion indicates a successful and effective reperfusion . In patients who have not received reperfusion therapies, early inverted T waves were shown to be a marker of spontaneous recanalization of the culprit artery . Therefore, in this case, the patient experienced the acute, typical chest pain of AMI, but it resolved spontaneously.…”
Section: Discussionmentioning
confidence: 79%
“…rise might be identified by an accurate indicator of spontaneous reperfusion of an infarct-related artery on the E.C.G. [37]. -segment portion from the baseline.…”
Section: T-wave Inversionmentioning
confidence: 99%
“…rise might be identified by an accurate indicator of spontaneous reperfusion of an infarct-related artery on the E.C.G. [ 37 ]. Value of the recently found T-wave inversion as a predictor in patients who have undergone first percutaneous coronary interventions and have elevated S.T.-segment MI (PCI).…”
Section: Reviewmentioning
confidence: 99%
“…Beberapa studi ini berhubungan dengan MI, yaitu terdapat hubungan antara invers gelombang T awal dan arteri terkait dengan MI. Posisi gelombang T yang terbalik secara bersamaan pada gelombang ST dapat menjadi penanda yang tepat untuk myocardial infarction [10]. Pada studi deteksi MI yang menggunakan gelombang EKG, peningkatkan akurasi dapat dilakukan menggunakan metode Multiple Instance Learning (MIL).…”
Section: Pendahuluanunclassified